Reinstatement of “Hippolyte St. Pauli” Brandt, 1851 as a valid species of Lebbeus White, 1847 (Decapoda: Caridea: Thoridae) - Komai, Tomoyuki; Lemaitre, Rafael (Zootaxa, 2022)
Comparison between materials from various localities in the North Pacific and North Atlantic, including specimens identified with Lebbeus polaris (Sabine, 1824) in previous studies, led the authors to reinstate “Hippolyte St. Pauli” Brandt, 1851 as a valid species of the thorid genus Lebbeus White, 1847 (Decapoda: Caridea), removed from the synonymy of L. polaris. Lebbeus sanctipauli is distinguished from L. polaris by the rostrum with fewer dorsal teeth in female and a better developed ventral blade in male, fewer dorsolateral spiniform setae on the telson (three or four, rarely five versus six to 12), the longer antennular stylocerite in females, stouter pereopods 3–5 with fewer accessory spiniform setae on pereopods 3–5 dactyli (three or four versus five to seven) and the possession of an epipod on the pereopod 3. Although L. polaris has been thought to have a circumpolar distribution, the occurrence of the species in the North Pacific Ocean needs to be verified.